1996
DOI: 10.1093/arclin/11.6.529
|View full text |Cite
|
Sign up to set email alerts
|

Screening for dementia of the alzheimer type in the community: The utility of the clock drawing test

Abstract: This study reports the sensitivity and specificity of the Clock Drawing Test (CDT) for detecting dementia of the Alzheimer type in a community-dwelling sample of elderly subjects. Forty-two patients with clinically diagnosed Alzheimer's disease and 237 cognitively intact subjects were administered the CDT as part of an epidemiological study of aging and dementia. Three individual measures of clock drawing performance (quantitative score, qualitative score, and combined quantitative and qualitative score) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
3
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(71 citation statements)
references
References 27 publications
1
66
3
1
Order By: Relevance
“…[28] In this study, the clock drawing test, with an AUC of 0.732, supported its utility as a dementia assessment [27] and confirmed earlier findings of its ability to differentiate normal from pathological cognitive decline. [29] However, the sensitivity of 44.4% in this study was much lower than the mean of 85% reported in the literature for dementia screening, while the specificity of 91.7% compared favourably with the specificity of 85% reported in the literature. [26] …”
Section: Screening For Overall Pathological Cognitive Declinecontrasting
confidence: 82%
See 1 more Smart Citation
“…[28] In this study, the clock drawing test, with an AUC of 0.732, supported its utility as a dementia assessment [27] and confirmed earlier findings of its ability to differentiate normal from pathological cognitive decline. [29] However, the sensitivity of 44.4% in this study was much lower than the mean of 85% reported in the literature for dementia screening, while the specificity of 91.7% compared favourably with the specificity of 85% reported in the literature. [26] …”
Section: Screening For Overall Pathological Cognitive Declinecontrasting
confidence: 82%
“…However, this finding may be owing to the non-clinical sample in this study, as neuropsychological tests are considered to be less accurate in community samples. [29] Screening for MCI MCI is widely regarded as an intermediate stage between Alzheimer's disease and normal ageing, and has a heterogeneous cognitive profile. [37,38] It is therefore recommended that an extensive range of domains be covered when assessing for MCI, including language, memory, executive functions and attention.…”
Section: Screening For Dementiamentioning
confidence: 99%
“…Based on the established cutoff points for vitamin D status, 11 16.6% (n ϭ 68) of our subjects had severe 25OHD insufficiency, 70.3% (n ϭ 289) moderate 25OHD insufficiency, and 13.1% (n ϭ 54) normal serum 25OHD concentrations. Subjects with severe 25OHD insufficiency had lower binocular visual acuity ( p ϭ 0.016) and walking speed ( p ϭ 0.002) compared to those with moderate 25OHD insufficiency (table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Cognitive decline was considered when the subject had an abnormal Clock Drawing Test and an abnormal episodic memory test. 16 Episodic memory test was built from the 6 memory items of Folstein's Mini-Mental State Examination (MMSE). 17 It was calculated as (immediate recall of the 3 recall items ϩ delayed recall of the 3 words).…”
mentioning
confidence: 99%
“…In the Class II Rancho Bernardo populationbased study, 199 patients over the age of 65 were designated as having possible cognitive impairment after undergoing an initial screen. 29 They were administered the CDT as were 203 age-matched normal elderly (screen negative) from the same population base. The cutoff scores were determined (using ROC curves) and resulted in sensitivity of 83% and specificity of 72% for the global scores.…”
Section: Brief Focused Screening Instrumentsmentioning
confidence: 99%